Analisis Kebutuhan Buku Bacaan Anak Berkecenderungan Visual Spasial - Lestari, Mas Roro Diah Wahyu; Syofyan, Herlinda; Aswir, Aswir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The problem in this study stems from the problem of decreasing literacy scores of elementary school children in south Tangerang below 75. The purpose of the study was to find indicators of book making that are able to make children tend to visually spatial like the books they read. This study used qualitatif research with data collection using Surveys.   There were 62 samples of grade 5 students who tend to think visual spatial The results of the study obtained the formulation of indicators in making books that are tailored for children who tend to think visual spatial. The findings formulate indicators for making storybooks for children to think visually spatial, that visual spatial children like many pictures with attractive color displays. They like comics because of the few sentences they read. They like simple language so that it is easy to understand.  They also like to read stories if there are similar cartoon characters they meet on television.